STRATEGIC ANALYSIS OF BUSINESS SOCIAL COMMUNICATIONS IN THE PROCESS OF EUROPEAN INTEGRATION TRENDS PROMOTING IN UKRAINE - Revenko , Olena; Revenko , Tetyana (Pressing Problems of Public Administration, 2021)
An important impulse for economic development is a system of factors shaping the effective operation of business. Management of any enterprise is impossible without planning its business activities, which is based on the results and conclusions of strategic analysis. In the context of European integration, Ukrainian business structures face a real problem of enterprise main activities harmonization and measures for their social responsibility. The aim of the research is to substantiate the directions of business development taking into account the concept of social responsibility on the basis of strategic analysis of social communications, which have its own specifics in the process of promoting trends of European integration in Ukraine.The components of the structural-functional scheme of providing social communications of business in the process of propagating the tendencies of European integration are theoretically substantiated. The key subsystem in this process is the organization of business structure social communications strategic analysis, which allows to identify their specifics, conditions of formation and mechanism of influence on business development in an integrated environment. The role of social communications in the process of promoting trends of European integration in Ukraine has been studied. The purpose of social advertising application by business structure on an example of classification of its technologies depending on the purpose of establishment of communication is considered. The general features of socially responsible business structures, as well as the applicability of social advertising technologies in their activities are also identified. It is concluded that such social communication allows to form certain values, in particular European ones, and to express the position concerning certain questions (ecological, medical, integration). The peculiarities of the strategic analysis of business social communications are singled out, the consideration of which will allow to make an effective process of their management on the basis of European values.